The Effectivenes of Managerial Skills of State Elementary School Principals in East Jakarta - Kemal, Isthifa; Setyanto, Eddy (Jurnal Ilmiah Peuradeun, 2017)
The purpose of this study is to determine the effectiveness of managerial skills of state elementary school principals in east Jakarta. The research involved 238 state elementary schools in east Jakarta and it had been selected from the target population of 588 state elementary school principals by using qualitative approach with path analysis methods. The research hypothesis testing showed that managerial knowledge had a positive direct effect on effective management. Therefore to improve the effectiveness of managerial skills of state elementary school principals in east Jakarta, thus management knowledge of education needed.